Principles of international criminal law - Werle, Gerhard, author; Jessberger, Florian, author (New York, NY ; Oxford, United Kingdom, 2014)
This edition builds on the highly-successful work of the previous editions, setting out the general principles governing international crimes as well as the fundamentals of both substantive and procedural international criminal law.
Foundations -- General principles -- Genocide -- Crimes against humanity -- War crimes -- The crime of aggression.
Includes bibliographical references and index
Keywords: Criminal procedure (International law); Criminal law -- International unification